Impact of an Antimicrobial Stewardship Strategy on Surgical Hospital Discharge: Improving Antibiotic Prescription in the Transition of Care - Alfredo Jover-Sáenz; Carlos Santos Rodríguez; Miguel Ángel Ramos Gil; Meritxell Palomera Fernández; Liliana Filippa Invencio da Costa; Joan Torres-; Dolors Castellana Perelló; Elisa Montiu González; Joan Antoni Schoenenberger-Arnaiz; Juan Ramón Bordalba Gómez; Xavier Galindo Ortego; María Ramirez-Hidalgo (MDPI AG, 2023)
Antimicrobial stewardship programs (AMSPs) are essential elements in reducing the unnecessary overprescription of antibiotics. Most of the actions of these programs have focused on actions during acute hospitalization. However, most prescriptions occur after hospital discharge, which represents a necessary and real opportunity for improvement in these programs. We present an AMSP multifaceted strategy implemented in a surgical department which was carried out by a multidisciplinary team to verify its reliability and effectiveness. Over a 1-year post-implementation period, compared to the pre-intervention period, a significant reduction of around 60% in antibiotic exposure occurred, with lower economic cost and greater safety.